Instilling Religious Moderation Value in ELT through Cross-Cultural Understanding Course - Nirwana, Nirwana; Darmadali, Waode Surya (Elsya : Journal of English Language Studies, 2021)
Religious moderation has become a new and unique issue discussed by the Ministry of Religion of the Republic of Indonesia. Universities are held to be a platform for promoting religious moderation through the learning process. Integrating religious moderation in the learning process is the main alternative to increase understanding of religious moderation in educational institutions, but there are only a small number of research and technical guidelines for subjects with a religious background such as Islamic religious education. Therefore, this study intends to instill religious moderation values in English language learning through cross-cultural understanding. The CCU course is suitable for negotiating an understanding between cultures and religions, especially in the context of the multicultural society of Indonesia. This research used a descriptive qualitative method, instruments being analysis sheets of RPS documents, research rubrics, and student learning outcomes in the CCU course, library research to obtain more detailed information on the value of religious moderation, field notes on observations in class; and an 8-item questionnaire. Results reveal that universities integrate religious moderation values, such as tolerance, national commitment, accommodating to the local culture, and anti-violence, into the learning process. The researcher connected religious moderation values with learning outcomes of CCU and implemented it in the learning process by using some methods such as group presentation, debating, watching a movie. This study proved that instilling religious moderation value through CCU course improved the students’ values, understanding and awareness of religious moderation. This study contributed to the Indonesian Ministry of Religion’s mission to make Islamic higher education a place for instilling the value of religious moderation, especially to students as the nation's future leaders and generation.